Revising the Standard Occupational Classification System. - Levine, Chester; Salmon, Laurie; Weinberg, Daniel H. (Monthly Labor Review, 1999)
Occupational data have been compiled in America since the 1850 census, but the modern Standard Occupational Classification (SOC) system was not developed until 1977. The SOC aims to include all occupations for which work is performed for pay or profit. There were flaws and omissions in the original SOC, so that the system was revised in 1980 to be used for tabulations from the 1980 decennial census. Despite plans for frequent reviews, the validity and effectiveness of the 1980 SOC for current needs were not studied until the mid-1990s. The writers discuss the new system for classifying occupations introduced in 1998, which reflected the many changes to the world of work in recent decades. Sidebars examine the occupational classification used in the 1850 census and the implementation of the 1998 SOC.